Comparing bioelectrical activity of the peripheral retina among myopic patients operated for rhegmatogenous retinal detachment complicated by choroidal detachment - Alibet Yassine; V.S. Ponomarchuk; G.V. Levytska; N.I. Khramenko (Ukrainian Society of Ophthalmologists, 2018)
Background: High myopia is known to be a major risk factor for the development of choroidal detachment (CD) in eyes with rhegmatogenous retinal detachment (RRD). Trophic disturbances of the retina in axial myopia have been previously confirmed by electroretinography (ERG) data, and are likely to play an important role in the pathogenesis of RRD complicated by CD. To the best of our knowledge, no study has examined in detail the ERG in myopic patients operated for RRD combined with CD. Purpose: 1) To investigate the bioelectrical activity of the peripheral retina after successful surgery for combined RRD and CD in patients differing in the degree of myopia, and 2) to compare the characteristics with those of normal eyes and myopic patients successfully operated for uncomplicated RRD. Materials and Methods: Fifty two patients (52 eyes) were included into the study 3 months after undergoing a single successful vitrectomy with gas tamponade, either for uncomplicated RRD (32 eyes), or combined RRD and CD (20 eyes). They were divided into four groups: Groups 1 and 2 (moderate and high myopes after surgery for uncomplicated RRD; 21 and 11 patients, respectively), and Groups 3 and 4 (moderate and high myopes after surgery for combined RRD and CD; 9 and 11 patients, respectively). Fourteen age-matched individuals (28 eyes) without any ocular or systemic disease were enrolled as controls (Group 5). Scotopic rod response, scotopic combined rod-cone response, and scotopic oscillatory potentials (OPs) were recorded to examine the bioelectrical activity of the peripheral retina. Results: The b-wave amplitude of scotopic rod-mediated response (the summed response of the midperipheral retinal layers to a weak flash arising from the rods in the dark-adapted eye) in myopic eyes in Groups 3 and 4 was 12-fold lower than in normal eyes, 4.3- to 8.8-fold lower than in the fellow eye, and 2.9- to 8.4-fold lower than in myopic eyes in Groups 1 and 2. In addition, the a-wave amplitude (the response of the peripheral retinal photoreceptors) in myopic eyes in Groups 1 and 3 was 1.8-fold lower than in normal eyes, and in highly myopic eyes, 3.4-fold lower than in normal eyes. The b-wave amplitude of scotopic combined rod-cone response (representing the activity of the midperipheral retinal layers) in Groups 3 and 4 was 2.5-fold and 7.5-fold lower, respectively, than in normal eyes, and 1.5-fold and 4.4-fold lower, respectively, than in the fellow eye, and 1.87-fold lower than in myopic eyes in Groups 1 and 2. The OP amplitude in myopic eyes in Groups 3 and 4 was 8.2-fold lower than in normal eyes, 4-fold lower than in the fellow eye, and 2.6- to 5.5-fold lower than in myopic eyes myopic eyes in Groups 1 and 2. The b-wave implicit time of scotopic combined rod-cone response in myopic eyes in Groups 1 to 4 was 19.9% (p < 0.05) longer than in normal eyes. In addition, myopic eyes in Groups 1 to 4 had similar a-wave implicit time compared with normal eyes. We found direct correlations between BCVA and b-wave and a-wave amplitudes of the scotopic rod-mediated response ERG (r = 0.59 and r = 0.67, respectively), b-wave amplitude of the scotopic combined rod-cone response ERG (r = 0.5), and OP amplitude (r = 0.62), and an inverse correlation (r=-0.63) between BCVA and b-wave implicit time for the scotopic combined rod-cone response ERG in myopic patients after surgery for combined RRD and CD. Conclusion: In myopic patients after surgery for combined RRD and CD, the bioelectrical activity of the peripheral retina was found to be low